We hold ourselves accountable: a relational view of team accountability - Stewart, Virginia R.; Snyder, Deirdre G.; Kou, Chia-Yu (Springer, 2021)
Accountability is of universal interest to the business ethics community, but the emphasis to date has been primarily at the level of the industry, organization, or key individuals. This paper unites concepts from relational and felt accountability and team dynamics to provide an initial explanatory framework that emphasizes the importance of social interactions to team accountability. We develop a measure of team accountability using participants in the USA and Europe and then use it to study a cohort of 65 teams of Irish business students over three months as they complete a complex simulation. Our hypotheses test the origins of team accountability and its effects on subsequent team performance and attitudinal states. Results indicate that initial team accountability is strongly related to team trust, commitment, efficacy, and identifying with the team emotionally. In established teams, accountability increases effort and willingness to continue to collaborate but did not significantly improve task performance in this investigation.
Keywords: Collective; Commitment; Felt accountability; Group; Longitudinal; Measure; Performance; Relational accountability; Team; Trust